Rare‐Earth Lanthanum Tailoring Mott–Schottky Heterojunction by Sulfur Vacancy Modification as a Bifunctional Electrocatalyst for Zinc–Air Battery. Issue 2 (23rd November 2022) - Yang, Zhou; Yang, Jingjing; Yu, Chengbin; Bai, Jirong; Xie, Xinjie; Jiang, Nan; Chen, Bingbing; Dong, Shuang; Xiang, Meng; Qin, Hengfei
Abstract : Zinc–air battery (ZAB) has considerable potential to be applied in the energy storage field. The main commercial electrocatalysts are Pt/C and RuO2, which are expensive and cannot possess good bifunctional electrocatalytic activities including oxygen reduction reaction and oxygen evolution reaction. Herein, the rare‐earth metal lanthanum is first constructed to be a Mott–Schottky heterojunction, and the S vacancy is introduced into the Mott–Schottky heterojunction. The so‐obtained La/La2 O2 S1− x shows excellent bifunctional electrocatalytic activity with Δ E of 0.68 V, which is superior to La/La2 O2 S without S vacancies and the commercial Pt/C + RuO2 system. In addition, the La/La2 O2 S1− x is assembled into ZABs, showing a high open power density of 212 mW cm −2, and a large specific capacity of 707 mAh g −1, as good cycle stability. The density functional theory calculations reveal the tailoring effect of S vacancy on the Schottky barrier to control the electron transfer concentration and ameliorate over‐strong adsorption, which blocks the reflux of electrons and promotes the unidirectional flow of electrons. In addition, the S vacancy modulates the electron cloud of La‐4 f orbit and makes the electrocatalytic pathway closer to the ideal pathway. Abstract : The high‐performance bifunctional electrocatalyst La/La2 O2 S1− x Mott–Schottky heterojunction is tailored by S vacancies to modulates the Schottky barrier and control the electron transfer, which ameliorates overstrong adsorption of pristine La/La2 O2 S in the electrocatalytic process and enhance the electrocatalytic performances. La/La2 O2 S1− x is applied in zinc–air battery to show good performances.